Model identification in computational stochastic dynamics using experimental modal data. (January 2015) - Batou, A.; Soize, C.; Audebert, S.
Abstract: This paper deals with the identification of a stochastic computational model using experimental eigenfrequencies and mode shapes. In the presence of randomness, it is difficult to construct a one-to-one correspondence between the results provided by the stochastic computational model and the experimental data because of the random modes crossing and veering phenomena that may occur from one realization to another one. In this paper, this correspondence is constructed by introducing an adapted transformation for the computed modal quantities. Then the transformed computed modal quantities can be compared with the experimental data in order to identify the parameters of the stochastic computational model. The methodology is applied to a booster pump of thermal units for which experimental modal data have been measured on several sites. Abstract : Highlights: A stochastic computational model is identified using modal data. A transform of the random modal quantities is introduced. Mode crossings and mode veerings are automatically taken into account. The methodology is applied to a booster pump of thermal units.